Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

The effect of LED wavelength variations on catch efficiency in Portunidae trap fisheries - Wei Yu Lee; Hui Xu; Muhamad Naimullah; Mhd Ikhwanuddin; Khor Waiho; Hanafiah Fazhan; Sukree Hajisamae; Yasuzumi Fujimori (Fisheries Science, 2026)

Abundance Variability of Predators: Asynchronous Fluctuation of Tuna Species in the Atlantic Ocean due to Predation Strategies and Climatic Effects - Ting‐Yu Liang; Kuo‐Wei Lan; Muhamad Naimullah; Yen‐Rong Liang; Yan‐Lun Wu (Fisheries Oceanography, 2025)
Bigeye tuna ( Thunnus obesus ; BET) and yellowfin tuna ( Thunnus albacares ; YFT) are commercially and ecologically important Atlantic Ocean species. Numerous studies have examined interacting species with clearly synchronous or asynchronous dynamics, but few have investigated interactions among tuna species. This study investigated the effects of climate indices on the standardized catch per unit effort (CPUE) and habitat preferences of BET and YFT in the Atlantic Ocean. The indicators for both tuna species were found to be influenced by the Atlantic Multidecadal Oscillation (AMO) and Tropical North Atlantic index. The AMO had the strongest effect on standardized CPUE for the two species, and habitat suitability also reflected AMO trends. We compared CPUE trends in overlapping suitable habitat areas and estimated variations in primary prey abundance for between BET and YFT to evaluate their species' competition for limited prey and habitat area resources. The standardized CPUE, habitat suitability index (HSI), and primary prey levels (squid and crustaceans) of BET all increased following the change to the positive AMO phase after the 1990s. Although the HSI value for YFT also increased in an area of habitat overlap, the corresponding standardized CPUE decreased. We suggest that this pattern of a decreasing‐standardized CPUE for YFT may have been caused by competition for limited prey and habitat area resources in the overlap area.

Feeding Behavior and Bait Selection Characteristics for the Portunidae Crabs Portunus sanguinolentus and Charybdis natator - Wei-Yu Lee; Yan-Lun Wu; Muhamad Naimullah; Ting-Yu Liang; Kuo-Wei Lan (Fishes, 2024)
Understanding the feeding behavior of Portunidae crabs with different baits can improve bait selection and is crucial for improving the effectiveness of crab fishing gear. This study, conducted in indoor experimental tanks, used trajectory tracking software and two types of natural baits (mackerel (Scomber australasicus) and squid (Uroteuthis chinensis)) to understand the behavior of Portunus sanguinolentus and Charybdis natator. Spatial distribution results showed that P. sanguinolentus was frequently present in the starting area (S1) and bait area (S3) in the control and treatment groups. However, C. natator was frequently present and concentrated in the S1 area compared to the middle areas S2 and S3, and only in the mackerel treatments were they observed to move to the S3 areas. The spatial distribution results indicate that P. sanguinolentus shows a stronger willingness to explore its surroundings, while C. natator is generally in a stationary, wait-and-see state. The swimming speeds of P. sanguinolentus and C. natator showed different trends. P. sanguinolentus showed continuous movement with no fixed speed when no bait was present in the control groups. However, when treated with mackerel and squid, the average swimming speed of P. sanguinolentus was faster (>5 cm/s) in the first 10 min and showed a more stable movement speed when searching for the baits. C. natator showed a stationary or low movement speed when no bait was present in the control groups. However, when C. natator perceived the presence of the baits in the treatment groups, their movement speed increased in the first 10 min. In addition, there was no significant difference between male and female crabs of P. sanguinolentus and C. natator in movement speed in the control and treatment groups. Compared to C. natator, P. sanguinolentus might be more sensitive to natural baits, as shown by its movement from S1 to S3. The results indicate that the species of Portunidae crabs show different bait selections. Natural baits (mackerel and squid) are recommended for catching P. sanguinolentus in crab fisheries.

Habitat changes and catch rate variability for greater amberjack in the Taiwan Strait: The effects of El Niño–southern oscillation events - Mubarak Mammel; Ming-An Lee; Muhamad Naimullah; Cheng-Hsin Liao; Yi-Chen Wang; Bambang Semedi (Frontiers in Marine Science, 2023)
El Niño–Southern Oscillation (ENSO) is a crucial oceanographic phenomenon that leads to interannual fluctuations in the climate and ecosystem productivity of tropical and subtropical areas. These fluctuations affect the suitability of habitats for many commercial fish species. However, detailed information on the effects of this major phenomenon and the resulting environmental changes on the habitat and catch rates of the economically and ecologically crucial species of the greater amberjack ( Seriola dumerili ) in the Taiwan Strait (TS) is lacking. In this study, we employed a weighted habitat suitability index (HSI) modeling method and used remotely sensed marine environmental data as well as data from recorders in Taiwanese fishing vessels (in 2014–2019) to understand the effects of ENSO events on the habitat suitability and catch rates for greater amberjack in the TS. Analysis of variance revealed that environmental factors substantially influenced greater amberjack habitats and catch rates during ENSO events across seasons. The catch rates were high in spring and summer in the southern and northern TS and in autumn and winter in the southern TS. The catch rates were higher in spring, summer, and autumn (>9.0 kg/h) in El Niño years, and in winter, the catch rates were higher in normal years (>12.0 kg/h) and lower in La Niña years. The predicted HSI for the southern and northern TS revealed that greater amberjack populations were predominantly distributed at 20–24°N and 24–28°N, respectively. Opposite habitat suitability was synchronously found in spring and summer during ENSO events, with higher HSI values recorded in spring in El Niño and normal years and higher HSI values recorded in summer in La Niña years. In winter, the HSI values of the southern and northern TS were higher in El Niño and normal years and substantially lower in La Niña years. Habitat suitability was extremely low in autumn. These findings imply that ENSO events play a key role in regulating environmental conditions and affect the catch rates and habitat suitability for the greater amberjack in the TS.

Species composition, abundance, size distribution, sex ratios, and movement of Scylla mud crabs within the mangrove ecosystem at Setiu Wetland, Terengganu, Malaysia - Hanafiah Fazhan; Mohamad N. Azra; Siti Aisah Halim; Muhamad Naimullah; Muyassar H. Abualreesh; Alexander Chong Shu-Chien; Youji Wang; Yushinta Fujaya; Mohammad Syahnon; Hongyu Ma; Khor Waiho; Mhd Ikhwanuddin (Frontiers in Marine Science, 2022)
The aim of the present study was to determine the movement patterns of mud crabs, genus Scylla , within the mangrove area of the Setiu Wetland in Terengganu, Malaysia. Mark-release-recapture technique were conducted during 24 sampling trips. A fluorescent visible implant elastomer (VIE) tag was inserted within the crab’s shell and they were released at the same capture stations over an interval of two weeks before the next sampling. A total of 288 crabs of various sizes, sex and species were identified, measured, tagged and recorded. The numbers of male crabs were higher than females. Three species were present, dominated by S. olivacea at 54.2% and S.tranquebarica at 26.4%, with S. paramamosain in third place at 19.4%. Among the 288 crabs that were tagged and released, 26.38% were recaptured. The tagged crabs did not move very far from the release station based on the recapture data. The greatest mean chance of being recaptured within 24 h was 44.5%, and there were no tagged crabs recaptured after 48 h even on sampling trips at several points from the release site. Knowledge of movement patterns is essential to understand migration and population dynamics and the relationship between reproduction and local distribution.

Distribution and Catch Rate Characteristics of Narrow-Barred Spanish Mackerel (Scomberomorus commerson) in Relation to Oceanographic Factors in the Waters Around Taiwan - Lu-Chi Chen; Jinn-Shing Weng; Muhamad Naimullah; Po-Yuan Hsiao; Chen-Te Tseng; Kuo-Wei Lan; Che-Chen Chuang (Frontiers in Marine Science, 2021)
This study investigated the relationship of the catch rates (CRs) of Spanish mackerel ( Scomberomorus commerson ) with oceanographic factors in the waters around Taiwan by using high-resolution fishery and environmental data for the period 2011–2016. The investigation results revealed that trammel nets accounted for 69.79% of the total catch of S. commerson and were operated mostly in the Taiwan Strait (TS). We noted seasonal variations in the distribution of high CRs. These CRs were observed in the southwestern TS, including the waters along the southwestern coast of Taiwan and around the Penghu Islands, and extended to the Taiwan Bank during autumn; they increased in winter. To predict the spatial and temporal patterns of Spanish mackerel density and their relationship with oceanographic and spatiotemporal variables, generalized additive models were used. These models explained 48.4% of the total deviance, which was consistent with the assumed Gaussian distribution. Moreover, all variables examined were significant CR predictors ( p < 0.05). Latitude and longitude were the key factors influencing the spatiotemporal distribution of S. commerson , and sea surface chlorophyll a concentration was a key oceanographic factor. Observing projected changes in El Niño/Southern Oscillation events for S. commerson revealed that CRs were higher and distributed further southward during La Niña events than during other events. We inferred that the S. commerson distribution gradually moved toward the southwest with the northeast monsoon, which was enhanced during La Niña in winter.

Effect of the El Niño–Southern Oscillation (ENSO) Cycle on the Catches and Habitat Patterns of Three Swimming Crabs in the Taiwan Strait - Muhamad Naimullah; Yan-Lun Wu; Ming-An Lee; Kuo-Wei Lan (Frontiers in Marine Science, 2021)
The swimming crabs is a crucial predator species in benthic habitats and a high value in commercial fishery industries in subtropical and tropical Asia. The climate variability caused by El Niño–Southern Oscillation (ENSO) events has substantial impacts on the catch and habitat of this species. In this study, a weighted habitat suitability index (HSI) model was constructed using logbooks and voyage data records from Taiwanese crab vessels (2013–2019) with the addition of environmental variables to examine the influence of ENSO events on catch rates (CRs) and habitat suitability for Charybdis feriatus , Portunus pelagicus , and Portunus sanguinolentus in the Taiwan Strait (TS). The autumn (September–October) is the major fishing season for catching these three swimming crab species in the TS. A high CR of P. sanguinolentus was observed across the TS, whereas high CRs of P. pelagicus and C. feriatus were recorded in areas in the southern and northern TS, respectively, during autumn. Moreover, the CRs for C. feriatus and P. pelagicus were higher (>7.0 and >8.0 kg/h) during La Niña events, with the increase being more than 40.0% compared with the CRs under normal and El Niño events in autumn. For P. sanguinolentus , the CRs were higher during both La Niña and El Niño events (>8.0 kg/h) compared with normal years. The high CRs for C. feriatus and P. sanguinolentus during autumn in La Niña years co-occurred with high sea temperature and low salinity, whereas the high CR of P. pelagicus co-occurred with high sea temperature and high salinity. Furthermore, the high CRs for C. feriatus and P. pelagicus were observed in areas with high HSI in the La Niña years but were distributed more widely with a lower HSI during normal and El Niño years. The low CRs for C. feriatus and P. pelagicus during normal and El Niño years and the low CR for P. sanguinolentus in normal years during autumn were highly consistent with substantial shrinkage of suitable habitats. Our findings suggest that ENSO events strongly affected the catch and habitat suitability of C. feriatus , P. pelagicus , and P. sanguinolentus during autumn in the TS.

Effects of Climate Change in Marine Ecosystems Based on the Spatiotemporal Age Structure of Top Predators: A Case Study of Bigeye Tuna in the Pacific Ocean - Kuo-Wei Lan; Yan-Lun Wu; Lu-Chi Chen; Muhamad Naimullah; Tzu-Hsiang Lin (Frontiers in Marine Science, 2021)
How top predators behave and are distributed depend on the conditions in their marine ecosystem through bottom−up forcing; this is because where and when these predators can feed and spawn are limited and change often. This study investigated how the catch rates of immature and mature cohorts of bigeye tuna (BET) varied across space and time; this was achieved by analyzing data on the Taiwanese longline fishery in the western and central Pacific Ocean (WCPO). We also conducted a case study on the time series patterns of BET cohorts to explore the processes that underlie the bottom-up control of the pelagic ecosystem that are influenced by decadal climate events. Wavelet analysis results revealed crucial synchronous shifts in the connection between the pelagic ecosystems at low trophic levels in relation to the immature BET cohort. Many variables exhibited decreasing trends after 2004–2005, and we followed the Pacific Decadal Oscillation (PDO) as a bottom-up control regulator. The results indicated that low recruitment into the mature cohort occurs 3 years after a decrease in the immature cohort’s food stocks, as indicated by a 3-year lag in our results. This finding demonstrated that, by exploring the connection between low-trophic-level species and top predators at various life stages, we can better understand how climate change affects the distribution and abundance of predator fish.